Subclinical Leaflet Thrombosis in Transcatheter and Surgical Bioprosthetic Valves: PARTNER 3 Cardiac Computed Tomography Substudy - Makkar, Raj R; Blanke, Philipp; Leipsic, Jonathon; Thourani, Vinod; Chakravarty, Tarun; Brown, David; Trento, Alfredo; Guyton, Robert; Babaliaros, Vasilis; Williams, Mathew; Jilaihawi, Hasan; Kodali, Susheel; et al. (Journal of the American College of Cardiology, 2020)
Subclinical leaflet thrombosis, characterized by hypoattenuated leaflet thickening (HALT) and reduced leaflet motion observed on 4-dimensional computed tomography (CT), may represent a form of bioprosthetic valve dysfunction. The U.S. Food and Drug Administration mandated CT studies to understand the natural history of this finding, differences between transcatheter and surgical valves, and its association with valve hemodynamics and clinical outcomes. The PARTNER 3 (The Safety and Effectiveness of the SAPIEN 3 Transcatheter Heart Valve in Low-Risk Patients With Aortic Stenosis) CT substudy randomized 435 patients with low-surgical-risk aortic stenosis to undergo transcatheter aortic valve replacement (n = 221) or surgery (n = 214). Serial 4-dimensional CTs were performed at 30 days and 1 year and were analyzed independently by a core laboratory. The incidence of HALT increased from 10% at 30 days to 24% at 1 year. Spontaneous resolution of 30-day HALT occurred in 54% of patients at 1 year, whereas new HALT appeared in 21% of patients at 1 year. HALT was more frequent in transcatheter versus surgical valves at 30 days (13% vs. 5%; p = 0.03), but not at 1 year (28% vs. 20%; p = 0.19). The presence of HALT did not significantly affect aortic valve mean gradients at 30 days or 1 year. Patients with HALT at both 30 days and 1 year, compared with those with no HALT at 30 days and 1 year, had significantly increased aortic valve gradients at 1 year (17.8 ± 2.2 mm Hg vs. 12.7. ± 0.3 mm Hg; p = 0.04). Subclinical leaflet thrombosis was more frequent in transcatheter compared with surgical valves at 30 days, but not at 1 year. The impact of HALT on thromboembolic complications and structural valve degeneration needs further assessment.